Gaya Kepemimpinan Demokratis terhadap Motivasi Guru dalam Meningkatkan Kualitas Pembelajaran: Studi Kasus SMPN 24 TompobuluKabupaten Maros - Jaya, Henra (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This study aims to determine the extent to which democratic leadership style affects teacher motivation in improving the quality of learning. Democratic leadership style is known for involving teachers in decision-making and giving them more autonomy, which is believed to increase motivation and involvement in learning activities. This study uses qualitative methods with interviews, documentation, observation and field notes distributed to a number of teachers in a school. The results of the study indicate that democratic leadership style has a positive and significant effect on teacher motivation, which ultimately contributes to improving the quality of learning. These findings provide insight for educational leaders regarding the importance of a participatory leadership approach in order to achieve optimal educational outcomes